Association between vitamin D level and insulin resistance among patients with type 2 diabetes mellitus in Sana’a City - Ali Salman Al-Shami; Mokhtar Alzumor; Adnan Aladhal; Abdulhakim Al-Saban (BMC Endocrine Disorders)
Abstract Background Numerous biological functions recognize vitamin D. The existence of vitamin D receptors on different tissues explains its diversity of actions. Insulin resistance and a higher risk of diabetes are associated with reduced levels of vitamin D. Objectives This study evaluated the association between vitamin D levels and insulin resistance in type 2 diabetic patients in Sana’a city. Methods This cross-sectional study included a total of 50 participants. Patients: Individuals aged 23 to 65 years. Control Group (Healthy Individuals): Interviews were conducted with patients aged 22 to 55 years diagnosed with type 2 diabetes mellitus to collect personal information, daily habits, dietary practices, and clinical characteristics. We assessed fasting blood sugar, vitamin D, insulin, and HbA1c as biochemical parameters. Body mass index (BMI) was calculated, and HOMA-IR and HOMA-β were measured in mmol/L as indicators of insulin resistance. A statistical software package was used for data analysis. Results Participants in the study ranged in age from 20 to 69 years. The study found that patients with type 2 diabetes mellitus had a 40% prevalence of vitamin D deficiency, compared to 20% in healthy individuals. Conclusions The findings indicate a significant association between low levels of vitamin D and insulin resistance, as measured by HOMA-B and HOMA-IR. Consequently, a deficiency in vitamin D among patients with type 2 diabetes mellitus may lead to increased insulin resistance.